Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica. Issue 6 (30th March 2018) - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A.; Corr, Hugh F.; Kohler, Jack; Olesen, Arne V.; Forsberg, René
Abstract: The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery‐Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future. Key Points: Topographical and hydrological controls of fast ice flow are identified in the Recovery/Slessor/Bailey Region We infer ancient ice flow coupling of Slessor and Recovery Glaciers through a deep, sharp gate in the bed topography Changes in ice sheet dynamics probably occurred and could reoccur in the Recovery/Slessor/Bailey Region